(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Research on improving methods for the synthesis of ion-exchange sorbents with a porous structure based on copolymers is relevant. The aim of this work is to obtain granular ion exchange sorbents based on acrylonitrile copolymers with multifunctional crosslinking agent - hexahydro-1,3,5-triakrililtriazinom by their chemical transformations and the study of their network structure.